2016
DOI: 10.4018/ijpada.2016010103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Organizational Citizenship Behavior on Perceptions of E-Filing Success

Abstract: Organizational citizenship behavior (OCB) and perceived organizational support (POS) have been explored extensively in the literature. highlights the need for more Information Systems (IS) research in this area. In this study the authors explore how technological advancements have improved the online tax filing process in the United States. In particular, we administered a survey to 102 Volunteer Income Tax Assistance program (VITA) Site Coordinators to explore the role of OCB and POS on user perceptions of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A. Brown, 2015; Carter, McFadden-Wade, & Wells, 2016; Karimikia, Singh, & Olesen, 2015), or a positive attitude (Campbell, White, & Johnson, 2003; Menning, Wilkinson, & Clarke, 1976; Shelby & Reinsch, 2003), there is a broad consensus that positive and negative emotions have different affects on message recipients but an overall agreement that in the vast majority of situations positive emotions have a more favorable affect on individuals and their organizations than do negative emotions. Developing these observations, Elliot and Thrash (2002) found that positive emotions promote resource building and collective involvement in goals.…”
Section: Results and Preliminary Findingsmentioning
confidence: 99%
“…A. Brown, 2015; Carter, McFadden-Wade, & Wells, 2016; Karimikia, Singh, & Olesen, 2015), or a positive attitude (Campbell, White, & Johnson, 2003; Menning, Wilkinson, & Clarke, 1976; Shelby & Reinsch, 2003), there is a broad consensus that positive and negative emotions have different affects on message recipients but an overall agreement that in the vast majority of situations positive emotions have a more favorable affect on individuals and their organizations than do negative emotions. Developing these observations, Elliot and Thrash (2002) found that positive emotions promote resource building and collective involvement in goals.…”
Section: Results and Preliminary Findingsmentioning
confidence: 99%
“…Although this scoping review selected 79 citations in the final inclusion, it only charted 10 out of 79 articles in this stage In addition, articles which discuss the topic in macro-levels (Economides & Terzis, 2008) and address local tax administration (Canares, 2016;Gonzalez et al, 2007) were also filtered out. Due to limitation to access full-text articles from publishers, for example the International Publisher of Information Science and Technology Research (http://igi-global.com), some research (Chen & Huang, 2009;Carter et al, 2016) could not be assessed for eligibility.…”
Section: Data Charting and Collationmentioning
confidence: 99%
“…These factors present themselves as constant in all countries where research about intentions have been conducted (Fu et al, 2006;Hung et al, 2006;Ojha et al, 2007;Liu et al, 2008;Warkentin et al, 2010;Carter et al, 2011a, b;Hussein et al, 2011;Lim et al, 2011;Stafford and Turan, 2011;Carter et al, 2012;Greenberg et al, 2012;Tan and Foo, 2012;Hastuti et al, 2014;Chen et al, 2015;Chaouali et al, 2016;Hammouri and Abu-Shanab, 2017;Zaidi et al, 2017). Second, other common factors identified are compatibility, ease of use, external influences, facilitating conditions, incentives, interpersonal or social influence, IT background or skills, national culture, optimism bias, perceived credibility, perceived organizational support, performance expectancy, prior experience, quality antecedents, IJAIM 27,2 relative advantage, self-efficacy, self-sufficiency and subjective norms (Wang, 2003;Fu et al, 2006;Hung et al, 2006;Ojha et al, 2007;Chen, 2010;Carter et al, 2011a,b;Carter et al, 2011a, b;Hussein et al, 2011;Carter et al, 2012;Tan and Foo, 2012;Liu and O'Farell, 2013;Hastuti et al, 2014;Chen et al, 2015;Carter et al, 2016;Chaouali et al, 2016;Hammouri and Abu-Shanab, 2017;Tarek et al, 2017;Zaidi et al, 2017). It must be pointed out here that some of the factors affecting behavioral intentions may be different among user groups (Hwan...…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of the latter, it was the Decomposed Model that was applied. Finally, three other models, the OCB, the IS Success and the IS Quality Models, were examined by the groups lead by Carter et al (2016), Chen et al (2015) and Chen (2010), respectively.…”
Section: Literature Reviewmentioning
confidence: 99%